Gastrointestinal Bleed from a Left Ventricle to Colonic Interposition Graft Fistula following an Esophagectomy - Abdulwahab Al Khalifa; William Gourdin McMaster Jr.; Colin Schieman; Richard Whitlock; Christopher Ricci; Matthew Danter (The Thoracic & Cardiovascular Surgeon Reports, 2017)
Colonic interposition grafts are commonly used as an esophageal conduit following esophageal resection. Significant morbidity is associated with this reconstruction due to the nature of the operation. Many of the complications associated with this procedure have clear management strategies; however, there is a paucity of data when it comes to managing rare complications. In this report, we discuss the presentation, operative intervention, and postoperative care of a patient who presented with a left ventricle to esophageal colonic interposition graft fistula.